2008
DOI: 10.1175/2007jcli1849.1
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Pacific SSTs: Linear Inverse Model Predictions of the PDO

Abstract: A linear inverse model (LIM) is used to predict Pacific (30°S-60°N) sea surface temperature anomalies (SSTAs), including the Pacific decadal oscillation (PDO). The LIM is derived from the observed simultaneous and lagged covariance statistics of 3-month running mean Pacific SSTA for the years 1951-2000. The model forecasts exhibit significant skill over much of the Pacific for two to three seasons in advance and up to a year in some locations, particulary for forecasts initialized in winter. The predicted and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
123
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(135 citation statements)
references
References 123 publications
5
123
0
2
Order By: Relevance
“…Finally, note that the MLR method bears some similarities to the use of linear inverse modeling in predictability studies (Newman 2007;Alexander et al 2008), but one difference is that, in linear inverse modeling, a single propagation operator is assumed valid for all forecast ranges, whereas we construct a different MLR operator for each forecast range. Hence, unless the AOGCMs examined here are exactly first-order Markov processes, in which case the linear inverse modeling assumption is valid, the MLR operators we use are necessarily more accurate.…”
Section: B Methodsmentioning
confidence: 99%
“…Finally, note that the MLR method bears some similarities to the use of linear inverse modeling in predictability studies (Newman 2007;Alexander et al 2008), but one difference is that, in linear inverse modeling, a single propagation operator is assumed valid for all forecast ranges, whereas we construct a different MLR operator for each forecast range. Hence, unless the AOGCMs examined here are exactly first-order Markov processes, in which case the linear inverse modeling assumption is valid, the MLR operators we use are necessarily more accurate.…”
Section: B Methodsmentioning
confidence: 99%
“…While the work of Keim et al (2002) was entirely retrospective, they suggested that PDO could be used to increase forecasting capability. Alexander et al (2008) developed a retrospective linear inverse model to predict Pacific sea surface temperature anomalies, including the PDO, which was useful in predicting PDO up to four seasons in advance. Their analysis indicated that much of the PDO variance was explained by ENSO teleconnections or a global trend.…”
Section: The Pacific Decadal Oscillation: a Primermentioning
confidence: 99%
“…Several studies have used linear inverse models (LIMs) derived from simultaneous and lagged covariance statistics of observed SST anomalies to better understand and predict ENSO (e.g. Penland and Magorian 1993;Penland and Sardeshmukh 1995); the springtime SFM SST pattern closely resembles the "optimal structure", the pattern identified in LIMs as the most likely to grow into a large ENSO event (Penland and Sardeshmukh 1995;Xue et al 1997;Thompson and Battisti 2001;Alexander et al 2008). In addition, there is a close correspondence between the development of SST anomalies predicted by LIM and the evolution of the atmosphere-ocean system indicated by the SFM prior to ENSO events (Alexander et al 2008).…”
Section: Introductionmentioning
confidence: 99%